Aerodynamic Analysis of Rotor Airfoils with Camber Morphing Mechanism versus Plain Flaps - Abdelmoula, A.; Grimm, F.; Yavrucuk, I.; Rauleder, J. (My University, 2023)
This study presents a comprehensive comparison between standard plain flap configurations and the FishBAC parabolic morphed camber concept. NACA23012 and SC1094R8 airfoils served as baseline configurations. Numerical simulations were performed with a free stream Mach number of M = 0:4 and angles of attack of a = [??5;astall ]. By analyzing deflection levels up to 4 percent of the chord and varying the starting point of camber morphing from 60% to 85% chord length, key aerodynamic parameters such as lift, lift-to-drag ratio, pitching moment, and center of pressure were evaluated. Both FishBAC and plain flap configurations showed significant lift improvements with increasing deflection levels, particularly in the case of FishBAC camber morphed airfoils and when camber morphing was shifted towards the trailing edge. Furthermore, the overall FishBAC configurations exhibited greater efficiency compared to the plain flap. As camber morphing was increased, the center of pressure shifted towards the trailing edge. The position of the center of pressure exhibited a remarkable sensitivity to the point at which the camber morphing started when the plain flap was applied. Higher deflections resulted in pronounced nose-down pitching moments compared to the baseline, which was most pronounced for the FishBAC camber morphed airfoils.
Keywords: Aerodynamics